Protests as “Events”: The Symbolic Struggles in 2013 Demonstrations in Turkey and Brazil - Mendonça, Ricardo Fabrino; Ercan, Selen A.; Ozguc, Umut; Reis, Stephanie Lorraine Gomes; Simões, Paula Guimarães (Revista de Sociologia e Política, 2020)
ABSCTRACT Introduction: The concept of “event” offers a valuable lens to understand the discursive contestations in and around protests. Events create ruptures that disturb the logic of continuity and open up new way of thinking and talking about the past and the future. Drawing on this concept, this article analyzes the 2013 protests in Turkey and Brazil. It investigates how the causes of these protests were framed and debated in each country and how these frames shifted over time by opening up new interpretations of the past and the future. Materials and Methods: Data is generated from four Facebook pages capturing the messages posted during the first 30 days of protests in each country. In the Brazilian case, we collected the posts of: (1) Passe Livre São Paulo (301,787 likes), the group that started the wave of protests; and (2) O Gigante Acordou (155,690 likes), a collective that emerged during the protests, representing nationalist perspectives. In total, 626 posts were collected from both pages. In the Turkish case, we analyzed posts that appeared on the pages of : (1) Taksim Dayanismasi (82,479 likes), an association that played a significant role in organizing and mobilizing Gezi Park protests; and (2) Recep Tayyip Erdogan (6,957,408 likes), a pro-government and inherently anti-protest page. We coded each post inductively focusing particularly on the way they framed the causes of the protests. We then identified the number of times each frame was mentioned during the first 30 days of the protests and explored whether and how frames changed over time. Results: Our analysis reveals a significant shift in the way the causes of the protests were framed over time in both countries, yet with different implications. While in Brazil, we observe a frame transformation undermining the initial rationale of the protests, in Turkey we see a frame extension and the emergence of broader issues as the real causes of protests, such as the authoritarian nature of the regime and the restriction of democratic rights in this country. Discussion: The article offers a way of analysing protests based on a conceptual lens of event. It sheds light on the role of social media as a platform for symbolic struggles over the protests. Furthermore, the article opens up a debate about the developments of democracy in both countries. KEYWORDS: events; protests; Gezi Park; June Journeys; Facebook. Protestos como “Acontecimentos”: as lutas simbólicas nas manifestações de 2013 no Brasil e na Turquia RESUMO Introdução: O conceito de “acontecimento” oferece uma perspectiva interessante para a compreensão de disputas discursivas nos protestos e sobre eles. Por “acontecimento”, entendemos rupturas da continuidade da experiência que alimentam disputas políticas pela reinterpretação de passados e futuros. Partindo do conceito e de sua utilidade para a leitura de disputas simbólicas, este artigo busca analisar os protestos de 2013 no Brasil e na Turquia. Investigamos como as razões a alicerçar tais protestos foram enquadradas e como esses enquadramentos mudaram ao longo do tempo, abrindo novas interpretações de passado e provendo novas possibilidades de imaginação do futuro. Materiais e Métodos: Dados foram gerados a partir de quatro páginas do Facebook, coletando mensagens postadas ao longo dos primeiros 30 dias de protestos em cada um dos países. No caso brasileiro, coletamos os posts de: (1) Passe Livre São Paulo (301.787 likes), o grupo que iniciou a onda de protestos; e (2) O Gigante Acordou (155.690 likes), um coletivo que emergiu durante os protestos, representando perspectivas nacionalistas. Ao todo, foram coletados 626 posts em ambas as páginas. No caso turco, analisaram-se posts que apareceram em: (1) Taksim Dayanismasi (82.479 likes), uma associação que teve papel significativo na organização e mobilização dos protestos do Gezi Park; e (2) Recep Tayyip Erdogan (6.957.408 likes), uma página pró-governo e essencialmente anti-protestos. Codificamos cada post indutivamente, enfocando, particularmente, o modo como eles enquadraram as causas dos protestos. Identificamos, então, a frequência de cada enquadramento nos 30 dias iniciais dos protestos e exploramos se, e como, isso se transformou ao longo do tempo. Resultados: A análise revelou a existência de viradas significativas na forma como as causas dos protestos foram enquadradas em ambos os países, mas com implicações distintas. Enquanto no Brasil, a “transformação de quadro” observada minou o foco inicial dos manifestantes, na Turquia, observa-se uma situação de “expansão do quadro”, com a tematização de questões mais amplas como causas dos protestos, como a natureza autoritária do regime e as restrições a direitos democráticos no país. Discussão: O artigo oferece uma maneira de analisar protestos com base na lente conceitual do “acontecimento”, esclarecendo o papel das mídias sociais no contexto das lutas simbólicas em torno dos protestos. Além disso, ele abre debate sobre as disputas de enquadramento a atravessar desdobramentos contemporâneos da democracia em ambos os países. PALAVRAS-CHAVE: acontecimento; protestos; Gezi Park; Jornadas de Junho; Facebook.